Sustainability Transition to Smart Agriculture—A Study Based on a Survey of Agricultural Planning by Prefecture in Japan - MARUKI, Hideaki; NOZU, Takashi; KAGEURA, Tomoya; WASHIZU, Ayu (ENVIRONMENTAL SCIENCE, 2024)
We positioned smart initiatives in the agricultural sector as niche innovations, and qualitatively evaluated the progress of these initiatives in each prefecture based on the sustainability transition methodologies. According to the results of a survey, the following were found for the prefectures that ranked high in initiatives. First, in the prefectures that these initiatives were progressing, promotion measures that met the transition management evaluation criteria were adopted according to the promotion plan, but there was no “flexible mechanism” or “mechanism to intervene without missing the right timing.” In addition, it was found that technologies related to the average price of products and the increase around farmland that can be cultivated by one person, smart technologies developed in the 2000s and 2010s, are being aimed at establishing them. Alternatively, prefectures that have not created concrete promotion plans for smart agriculture but have detailed prospects for smart agriculture in their higher-level agricultural plans, lack specific management measures for innovation. However, in those prefectures the changes in the landscape were accurately grasped and a broad outlook was made. These prefectures were also challenging new innovations such as carbon storage and acquisition of Good Agricultural Practices certification.